(untitled) (Journal of Parents and Teachers, 2013)
The great strategic decisions regarding ICT in schools and in the educational sector don’t have to be designed only by ICT coordinators. The ICT landscape has always to be at the project service helping professionals to achieve their goals. The boards and the steering teams have also to participate in the definition of the ICT strategy, aligning it to the pedagogical objectives as much as possible. This is crucial, because a good technological landscape in a school can be an amazing lever for learning.